NATIONALISM IN THE SONG LA MARSEILLAISE: A CRITICAL DISCOURSE ANALYSIS - Saputri, Nia Liska; Hadi, Irfan (Asosiasi dosen IDEBAHASA KEPRI, 2025)
Discourse of nationalism found in the French national anthem La Marseillaise was examined. The French Republic is recognized as a country in Western Europe and also characterized by several overseas islands and territories located across other continents. A critical discourse analysis framework developed by Norman Fairclough was applied in this study. Fairclough’s model was also selected due to its emphasis on linguistic analysis to assess sentence coherence. Additionally, coherence and cohesiveness were considered in terms of how words and sentences are combined to construct meaning and understanding through macro and micro structures. The central issue addressed in this research was how the theme of nationalism portrayed in the lyrics of La Marseillaise. In addition, it has a purpose to present the theme of nationalism as embedded in the lyrics of the anthem. To analyze it, qualitative content and descriptive analysis techniques had been employed. For data collection, content analysis procedures were utilized, including note-taking, translation, and consultation of relevant sources. The song La Marseillaise conveys themes of nationalism and patriotism through the interpretation of its lyrics. At the macro level, the lyrics clearly reflect patriotic sentiment by invoking a spirit of resistance and unity among the French people. Meanwhile, the micro-level analysis identified two prominent underlying motives: the motive of struggle and the motive of nationalism. However, based on the qualitative dominance of the microstructural elements, the nationalism motive emerges as the more salient of the two.